2012
DOI: 10.1111/j.1742-4658.2012.08611.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary relationship of the transcriptionally active fabp11a (intronless) and fabp11b genes of medaka with fabp11 genes of other teleost fishes

Abstract: Here we describe the structure of the fatty acid-binding protein 11a and 11b genes (fabp11a and fabp11b) in medaka, and their evolutionary relationship to fabp11 genes from other teleost fishes. Initial studies indicated that the medaka fabp11a gene is intronless, but the fabp11b gene consists of four exons separated by three introns, a genomic organization that is characteristic of most members of the intracellular lipid-binding protein family. Based on genomic sequence, we conclude that the intronless fabp11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The particular FABP gene identified in this study was originally reported in the heart of long-fingered ice fish (Cryodraco antarticus) [36] but is nowadays more commonly referred to as teleost-specific fatty-acid binding protein-11 (fabp11) [37]. Interestingly, duplicate genes (fabp11a and fabp11b) have been identified in zebrafish, three-spined stickleback (Gasterosteus aculeatus), fugu (Takifugu rubripes), spotted green pufferfish (Tetraodon nigroviridis), medaka (Oryzias latipes) [38], and rainbow trout (Oncorhynchus mykiss) [35].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The particular FABP gene identified in this study was originally reported in the heart of long-fingered ice fish (Cryodraco antarticus) [36] but is nowadays more commonly referred to as teleost-specific fatty-acid binding protein-11 (fabp11) [37]. Interestingly, duplicate genes (fabp11a and fabp11b) have been identified in zebrafish, three-spined stickleback (Gasterosteus aculeatus), fugu (Takifugu rubripes), spotted green pufferfish (Tetraodon nigroviridis), medaka (Oryzias latipes) [38], and rainbow trout (Oncorhynchus mykiss) [35].…”
Section: Discussionmentioning
confidence: 88%
“…Despite the limited information about both membrane-bound and cytoplasmic FABPs in the ovary of fish [2], these proteins are thought to act as regulators of fatty-acid metabolism and of bioavailability by facilitating the transport of long-chain fatty acids through the cytoplasm to the site of their oxidation. FABPs are also thought to facilitate fatty acid transport for further lipid-signalling pathways as well as support overall lipid homeostasis [2,35,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Aqp3 can reduce the differentiation and inhibit the apoptosis of stem cells in human through reducing the expressions of related genes in Wnt/GSK-3 β/β-catenin pathway (Liu et al, 2020). Fabp11a were probably involved in cellular uptake and transport of fatty acids, targeting of fatty acids to transport systems and several signalling pathways in Oryzias latipes (Parmar et al, 2012). In this study, all of these genes expression suggested that skin color variation of red tilapia during overwintering might be related to the proliferation, migration and differentiation of melanocytes.…”
Section: Discussionmentioning
confidence: 50%
“…Atotal of 12 FABP genes have been identified in vertebrates until now, but not all members of FABP genes occur in the same species [4]. For example, FABP10 and FABP11 have only been proposed in nonmammalian vertebrates, like teleost fishes [5], while FABP12 appears restricted to mammals, such as human [6]. All vertebrate FABP genes possess four exons separated by three introns [7], and contain a classical three-element finger print domain shared by three motifs termed FATTYACIDBP 1-3 (Kyoto Encyclopedia of Genes and Genomes; PRINTS: PR00178) [8].…”
Section: Introductionmentioning
confidence: 99%